Impact of Encroachment and Hyderabad City Effluents on Pinyari Canal - Mahessar, A. A.; Ansari, K.; Qureshi, A. L.; Mukwana, K. C.; Pathan, A. A.; Kori, S. M. (Engineering, Technology & Applied Science Research, 2020)
Pinyari canal off-takes from the left bank of Kotri barrage with a design discharge of 13,636 cusecs which passes through the ridge of Hyderabad city along with New Fuleli Canal and Akram Wah on its left side. Its water is used for irrigation, agriculture, industrial, domestic, and drinking purposes in Hyderabad and Sajawal districts in Sindh. This canal is non-perennial. Water is being released with low discharge only for drinking purposes during the dry season and with full supply in the wet season. The global water quality issue reflects the major impact of socioeconomic development and population growth changes on freshwater resources including canals and rivers. This paper presents the impact of untreated wastewater disposal to the canal. The practice of disposing of untreated effluents has created serious health and environmental problems for the locals. The statistical and geospatial tool GIS has been used for the assessment of water quality with visualization of wastewater behavior in the canal. The results of the statistical analysis showed that pH was within the permissible limits but Electric Conductivity (EC), Total Dissolved Solids (TDS), Sodium (Na), and Hardness exceed them. The Water Quality Index of the samples rated from very poor to unsuitable for drinking, hence, canal water is unfit for domestic use or drinking purposes.